Programmed - Aimed Approach to Sustainable Development Management. Regional Experience - TUREKULOVA, Dametken; SATKANOVA, Rimma; YESTURLIEVA, Aigul; BERMUKHAMEDOVA, Galiya; ASTAUBAYEVA, Gulnar (Journal of Environmental Management and Tourism, 2018)
Author исследует управление процессом разработки, реализации, мониторинга и оценки Программы развития территории на материалах Карагандинской области. explores the management of the developing, implementation, monitoring and evaluation of Program on the territory development based on the regional materials to measure sustainability. Выявленные в результате анализа проблемные зоны всех этапов управления государственной Программой развития территории за период с 2011-2015 года рассмотрены в работе с позиций мирового опыта оценки эффективности. The analysis the problem areas of all stages of management of the state program of territory development was used as starting point in assessing the effectiveness of public policy. В исследовании предпринята попытка решить теоретические и практические проблемы повышения эффективности государственного управления устойчивым развитием региона посредством улучшения методического обеспечения государственной Программы развития территории. The study reveals the attempt to solve theoretical and practical problems of increasing the efficiency of public administration in sustainable development of the region by improving the methodological support of the state program of development of the territory. Актуальность темы исследования . The New Methodology ofpublic public management , ориентированного на результаты, вопрос обеспечения экономической эффективности при соблюдении баланса интересов общества и природы становится актуальным для государственных органов, реализующих политику устойчивого развития в разрезе регионов. Management which is results-oriented, the issue of cost-effectiveness while balancing the interests of society and nature becomes relevant for governments implementing policies for sustainable development across the regions. State program being a sophisticated tool of state regulation, is a set of projects (measures) and regulatory instruments. Она требует взаимодействия большого количества субъектов разного уровня в процессе разработки, организации и координации усилий участников программы, мониторинга, оценки промежуточных результатов для обратной связи и корректировки программы, и, наконец, оценки конечных результатов, которая позволяет судить об эффективности программы и достижении поставленных целей.It requires the cooperation of a large number of different levels of actors in the development, organization and coordination of the efforts of participants in the program, monitoring and evaluation of interim results for the feedback and adjustment programs, and finally, evaluation of outcomes, which allows you to judge the effectiveness of the program and the achievement of its goals.